Characterization of rubberized cement-stabilized roadbase mixtures - Farhan, Ahmed Hilal (2016)
Due to urbanization, industrialization and population increase, a substantial increase occurred in the number of vehicles and hence large numbers of end-of-use tires are being disposed every year. The vast majority of these tires are stockpiled or used as a fuel for combustion which, in both cases, affects the environment detrimentally. The use of tire rubber in cement-stabilized aggregate mixtures (CSAMs) will ensure beneficial use of large quantities of these waste materials, saving natural resources and may enhance the properties of CSAMs especially these related to brittleness and sensitivity to fatigue failure.